2003
DOI: 10.1002/cncr.11389
|View full text |Cite
|
Sign up to set email alerts
|

Detection of micrometastasis of neuroblastoma to bone marrow and tumor dissemination to hematopoietic autografts using flow cytometry and reverse transcriptase‐polymerase chain reaction

Abstract: BACKGROUNDThe identification of neuroblastoma metastases to bone marrow (BM) is requisite in staging disease for risk‐adopted therapy. However, micrometastases were not elucidated fully.METHODSFlow cytometry (FCM) with CD45/CD56/CD81 and reverse transcriptase‐polymerase chain reactions (RT‐PCR) for tyrosine hydroxylase (TH) transcripts were used to evaluate neuroblastoma in bilateral BM aspirates at diagnosis, BM autografts, peripheral blood stem cell (PBSC) collections, and CD34+ cell products of 27 children.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 47 publications
(48 reference statements)
1
18
0
Order By: Relevance
“…This method has also been used to identify circulating and/or micrometastatic tumor cells in adult patients with carcinoma and was proved to be a significant prognostic factor in patients with prostate cancer and breast carcinoma (11,12). In pediatric patients, micrometastatic cells were detected in neurobalstoma and rhabdomyosarcoma (13)(14)(15). Only a few reports used FC for the diagnosis of ES tumors for the combination of CD45À/CD99þ (22,27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This method has also been used to identify circulating and/or micrometastatic tumor cells in adult patients with carcinoma and was proved to be a significant prognostic factor in patients with prostate cancer and breast carcinoma (11,12). In pediatric patients, micrometastatic cells were detected in neurobalstoma and rhabdomyosarcoma (13)(14)(15). Only a few reports used FC for the diagnosis of ES tumors for the combination of CD45À/CD99þ (22,27).…”
Section: Discussionmentioning
confidence: 99%
“…It is also used for diagnosis and follow-up evaluation in solid tumors, including breast and prostate cancer (11,12) in adult patients and rhabdomyosarcoma and neuroblastoma in pediatric patients (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…Expression of individual genes is often unreliable (47), and some in vitro differentiation markers, such as tyrosine hydroxylase and neuron-specific enolase, are markers of metastasis (48) and poor prognosis (49,50) when used clinically. In our meta-analysis of a microarray data set, none of the in vitro differentiation markers we used elsewhere correlated with stage of disease or TGFBR3 expression (data not shown).…”
Section: Figurementioning
confidence: 99%
“…The glycoprotein CD24 was investigated as a candidate unique identifier for the TIC in our neuroblastoma tumor spheres as this antigen has been shown to be expressed on renal cell carcinomas, small-cell lung carcinomas, and neuroblastomas (36,37). The hematopoietic progenitor marker CD34 was investigated as a potential unique identifier of the TIC in our neuroblastoma tumor spheres because several studies suggested that a small number of neuroblastoma cells in the bone marrow expressed CD34 and might be present in sufficient numbers in autologous bone marrow transplants to cause relapse (38)(39)(40)(41). We observed the presence of a small fraction of CD24 + (f0.24%) and CD34 + (f3.04%) cells in our highrisk neuroblastoma tumor spheres derived from bone marrow aspirates (Fig.…”
Section: Tumor-initiating Cells In Childhood Neuroblastomamentioning
confidence: 99%